Review Artikel : Analisis Pengaruh Kepatuhan Dalam Mengonsumsi Tablet Fe Pada Ibu Hamil - Christina Febiola Lubis; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Anemia in pregnant women is a condition of iron deficiency in the blood during pregnancy. The adverse effects of anemia in pregnant women on the fetus are stunted fetal growth, premature birth, babies with congenital defects, low birth weight (LBW), and fetal death in the womb. Meanwhile, the impact of anemia on pregnant women is difficulty breathing, fatigue, fast heartbeat, high blood pressure, insomnia, and an increased risk of bleeding. This research was conducted using a literature review study method. Data search was carried out using internet searches with references that match the criteria that will be used as a source for further research. To reduce the rate of anemia in pregnant women and reduce the adverse effects on mothers and babies due to anemia, this can be overcome by dutifully consuming Fe tablets. Compliance of pregnant women in consuming Fe tablets in dosage accuracy, method accuracy, and frequency accuracy. Consuming iron tablets will not reduce anemia if adherence to the consumption of Fe tablets is still low. Consuming Fe tablet supplementation based on the right time and method can increase the amount of haemoglobin.